Wireless LAN Network Authentication Captive Portal - Nita Rosa Damayanti; Sobri, Muhammad (International Journal of Computer, Network Security and Information System, 2020)
The development of wireless networks is needed to improve security and comfort when using it because of the current management of the hotspot network at PT. Tri Sapta Jaya which uses the old system has many shortcomings because there is no monitoring system and the use of the same password for each user and there are no data restrictions. To overcome these shortcomings, a new system is needed, using the Mikrotik Routerboard-based Captive portal authentication system that can be used to create an account for each different user to log in to the portal that will appear in the browser when connected to the network and the administrator can monitor devices that are connected to the network. hot spot. In research to develop the Captive portal system several stages are carried out using the waterfall system development method, namely analysis, design, implementation, testing and maintenance, in which case the research can produce a security system that runs optimally, safely, comfortably and efficiently.